2024
DOI: 10.1037/men0000448
|View full text |Cite
|
Sign up to set email alerts
|

Establishing research priorities for investigating male suicide risk and recovery: A modified Delphi study with lived-experience experts.

Susanna Bennett,
Kathyrn A. Robb,
Johnny Andoh-Arthur
et al.

Abstract: This study uses the Delphi expert consensus method to work with lived-experience experts and establish research priorities to advance our understanding of male suicide risk and recovery. Items for the Delphi were generated via findings from two recent quantitative and qualitative systematic reviews on male suicide, a comprehensive gray literature search, responses to a global survey on male suicide, and feedback from a panel of 10 international academic/clinical male suicide experts. A two-round Delphi study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Although they were not significant in the multivariate models, this study highlights the need for future early intervention programmes to consider these associations and for future research to account for these variables in order to create more conclusive evidence for the risk factors of suicidality among male construction workers. This study responded to recent calls for a better understanding of the relationship between mental health conditions and male suicide risk [68]. This study found that depression and anxiety is associated with suicidal ideation, NSSI and suicide attempts among male construction workers.…”
Section: Discussionmentioning
confidence: 77%
“…Although they were not significant in the multivariate models, this study highlights the need for future early intervention programmes to consider these associations and for future research to account for these variables in order to create more conclusive evidence for the risk factors of suicidality among male construction workers. This study responded to recent calls for a better understanding of the relationship between mental health conditions and male suicide risk [68]. This study found that depression and anxiety is associated with suicidal ideation, NSSI and suicide attempts among male construction workers.…”
Section: Discussionmentioning
confidence: 77%
“…Findings suggest females are more likely to be exposed to and influenced by friends' self-harm ideation and behaviour, as well more likely to be supporters and to experience the negative outcomes associated with the role (e.g., 98,94,78 ).This potentially relates to same-sex friendships and self-harm (NSSI) being more numerically prevalent in this age/gender group 123 , as opposed to males which typically present higher rates of suicide 124 . However, recent evidence suggests that gender differences in rates of self-harm ideation and behaviour may be unreliable, especially since male suicidal attempts may be underreported 125 . This suggests that investigation of understudied genders such as males and gender minorities is now needed given evidence of a) different friendship dynamics 126 , b) particular trajectories of mental health struggles, c) specific barriers/challenges in accessing support 127 and d) important benefits from peer support 127 and tailored interventions 74 among these populations.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, men who are lonely and/or socially isolated might be at higher risk due to lacking opportunities to benefit from protective support when experiencing suicidality-related distress (Subtheme 2.1). Loneliness and isolation, collectively, are key male suicide prevention research topic among lived experience experts (Bennett et al, 2024). Both experiences are strongly associated with suicidal ideation, cross-culturally, in men and women (Calati et al, 2019), whereas connectedness may have a buffering effect against suicidality (Arango et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One avenue for exploration is the role of masculinities, that is, individual and cultural meanings linked to men and boys (Wong & Wang, 2022). The influence of masculinities upon suicidal ideation and behaviors has been raised within psychological practice guidelines (American Psychological Association, 2018) and as a research priority by men with lived experience of suicide ideation, attempts, or bereavement (Bennett et al, 2024).…”
Section: Conceptualizations Of Masculinitiesmentioning
confidence: 99%